Effects of curcumin on the pharmacokinetics of amlodipine in rats and its potential mechanism - Na Jiang; Meicheng Zhang; Xiangzhi Meng; Bin Sun (Taylor & Francis Group, 2020)
Context Hyperlipidaemia and hypertension are often treated together with curcumin and amlodipine. It is necessary to investigate the drug-drug interaction between curcumin and amlodipine. Objective The interaction between curcumin and amlodipine was investigated in rats and with rat liver microsomes. Methods The pharmacokinetics of amlodipine (1 mg/kg) was investigated in rats with or without curcumin pre-treatment (2 mg/kg), six rats in each group. The metabolic stability of amlodipine was investigated with rat liver microsomes. Results Curcumin significantly increased the Cmax (26.19 ± 2.21 versus 17.80 ± 1.56 μg/L), AUC(0-t) (507.27 ± 60.23 versus 238.68 ± 45.59 μg·h/L), and t1/2 (14.69 ± 1.64 versus 11.43 ± 1.20 h) of amlodipine (p < 0.05). The metabolic stability of amlodipine was significantly increased with the half-life time in rat liver microsomes increased from 34.23 ± 3.33 to 44.15 ± 4.12 min, and the intrinsic rate decreased from 40.49 ± 3.26 to 31.39 ± 2.78 μL/min/mg protein. Discussion and conclusions These results indicated that drug-drug interaction might appear during the co-administration of curcumin and amlodipine. The potential mechanism may be due to the inhibition of CYP3A4 by curcumin. Thus, this interaction should be given special attention in the clinic and needs further experiments to characterize the effect in humans.